Coping with depression, anxiety, and stress: a cross-sectional study among Malaysian students in a public university - Mohammed, Hassan; K. S., Hayati; Salmiah, M. S. (International Organization of Scientific Research, 2016)
Depression, anxiety, and stress start at an early developmental stage of anadolescent. They increase the vulnerability of students, increase thesusceptibilityto minor and sometimes severe mental illnesses. The aim of this study is to determine the prevalence of depression, anxiety, and stress, coping strategies and other factors among first-year undergraduates. A cross-sectional study was conducted among 675 students of Universiti Putra Malaysia (UPM) using cluster sampling method. A self-administered questionnaire was used consisting of socio-demographic, environmental and socio-economic questions, DASS-21 and Brief-COPE inventory. The Majority of respondents were female, aged 20-21, Malay and Muslim. The majority of respondent’s parents had a diploma/university education, worked in government, father earned RM 2,500 or less and mothers had no monthly income. The prevalence of depression, anxiety, and stress was 32.1%, 64.6%,and 29.2% respectively. Factors associated with depression were gender, age, study major, parent’s education and occupation. Anxiety was associated with study major and parent’s education. Stress was associated with mother’s income, parent’s education and occupation. Mental illnesseshave implications on psychological morbidity and effect student’s health, development, education attainment and quality of life. More attention is needed in developing more support services, intervention strategies, screening and creating more awareness.